Super Graceful Labeling For A Class of Trees - Purwanto, P; Rahayu, Ariska Puji (Prosiding Konferensi Nasional Penelitian Matematika dan Pembelajarannya, 2019)
Let be a graph having vertex set , edge set , number of vertices | | , and number of edges | | . A super graceful labeling is a bijection function such that | | for every . A graph is called a super graceful graph if it admits a super graceful labeling. A tree is a tree obtained from a star on vertices by joining each vertex (one vertex if ) of degree 1 , , , to different new vertices . Super gracefulness of many classes of graphs, including special classes of trees, has been studied in the literature. In this paper we present a super graceful labeling of the tree .